2017
DOI: 10.4103/jmh.jmh_60_16
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of transcutaneous electrical nerve stimulation in the treatment of chronic pelvic pain

Abstract: Background:Chronic pelvic pain is prevalent in 2% of women population globally. The etiology is multifactorial. Even in the absence of pelvic pathology, there is a subgroup of women who do not respond to analgesic and anti-inflammatory therapy. Chronic pelvic pain can be inhibited by direct inhibition of impulses in the preganglionic afferent neuron by closing the hypothetical gate in the dorsal horn of the spinal cord. Transcutaneous electrical nerve stimulation (TENS) is based on the gate control theory of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 15 publications
2
44
0
1
Order By: Relevance
“… 8 , 29 Also, a similar pain reduction effect of TENS was noted for chronic prostatitis and chronic pelvic pain. 12 , 30 …”
Section: Discussionmentioning
confidence: 99%
“… 8 , 29 Also, a similar pain reduction effect of TENS was noted for chronic prostatitis and chronic pelvic pain. 12 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…34,35 A prospective study utilizing TENS for the treatment of pelvic pain showed reduced visual analog scale (VAS) pain scores compared to placebo group after 2 weeks of use. 36 Additionally, a Cochrane review evaluating efficacy of TENS for primary dysmenorrhea found highfrequency TENS more effective than placebo for pain relief. 37…”
Section: Neuromodulationmentioning
confidence: 99%
“…Pharmacological therapies for pain and inflammation are recognized and accepted by international medical guidelines as the first line of treatment. However, due to intolerable side effects (e.g., gastritis, nausea, and vomiting) [ 1 ] or the ineffectiveness of these interventions in some individuals, analgesic and nonpharmacological treatments with minimal side effects are necessary [ 2 ]. In this case, transcutaneous electrical nerve stimulation (TENS) is a physiotherapeutic resource that has been increasingly studied as an alternative therapy.…”
Section: Introductionmentioning
confidence: 99%
“…TENS has been used since 1970 as adjunctive therapy for acute and chronic pain management in various medical and surgical conditions [ 3 ]. Currently, evidence on the efficacy of TENS in clinical practice has not yet provided a definitive conclusion as to the clinical effects TENS is capable of generating, whether analgesic or nonanalgesic [ 1 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation